Risk Management in the Implementation of the Occupational Safety and Health System (SMK3) in the PLN Maluku and Papua Substation Project - Yunita Palik; Dewi Ana Rusim; Mujiati Mujiati; Bernathius Julison; Bahtiar Bahtiar; Duha Awaluddin Kurniatullah (Jurnal Indonesia Sosial Teknologi, 2024)
This research involves several PLN substation projects in the Maluku and Papua regions. The subject of this study consisted of 25 respondents, namely 1 Project Manager, HSE Engineer and project supervisor. The questionnaire that has been given is then analyzed using the severity index method. The results of K3 risk identification on 44 risk variable indicators with high variables are found in the categories of product purchase and control, work safety in SMK3 and monitoring standards. The highest level of K3 risk to cost performance in substation construction projects in Maluku and Papua is the specification of the purchase of goods and services, the verification system of purchased goods and services, emergency planning and recovery, and labour health monitoring. The allocation of K3 risk in substation construction projects in Maluku and Papua is the most allocated risk shared between the owner and the contractor. The most K3 risk response is by holding and partially allocating to the owner by transferring. Recommendations for mitigation of K3 risks in substation construction projects in Maluku and Papua are by preparing procedures for work steps/related documents that are jointly supervised between the owner and owner. Then it is necessary to form an organization related to K3 that will be responsible for emergencies, work accidents and monthly reporting to the local Manpower Office.